Advanced analysis and lightweight design of annular extrusion dies - Nie, Yi (2018)
Annular extrusion dies have been widely used for the production of plastic pipes and tubes. But they are usually designed according to engineering experience which has led to the overweight and waste in material of them. With increasingly stringent environmental regulations in many countries, attaining lightweight design of mechanical parts and components becomes an ever-lasting goal of designers during design process. Thus a systematic lightweight design methodology which integrates the tools of numerical simulation, structural optimization and life cycle assessment is proposed for annular extrusion dies in the thesis. The implementation of the lightweight design depends on the numerical simulation to model the coupled fluid-thermal-structural process of a typical extrusion operation. The simulation begins with the prediction of the rheological behaviours of polymer melts flowing through an annular extrusion die. The essential flow characteristics including velocity, pressure drop, wall shear stress and temperature are investigated. The Smart Bucket Surface mapping algorithm is then applied to transfer the temperature and pressure loads on flow channel for the following thermal and structural analysis of the extrusion die. The finite element analysis software ANSYS workbench 15.0 is used to calculate the temperature, deformation and thermal stress distribution of the die body. The effects of structure parameters and processing parameters on both the flow pattern of polymer melts and the mechanical properties of the die body are further investigated. Besides, a deformation and high temperature stress measurement system for the extrusion die is constructed using the corresponding sensors and data logger. The measurement results are compared with the simulation results which indicates the effectiveness of the proposed numerical model. Lightweight design of the extrusion die is then conducted using structural optimization. The design parameters and their threshold values which indicate the required performances of productivity, static stiffness, static strength, and manufacturability are identified according to the above numerical simulation results. The Adaptive Response Surface Method (ARSM) is used to solve the optimization scheme to achieve the targeted design parameters with minimum mass. The so-called lightweight coefficient is employed to characterize and evaluate the lightweight designed extrusion die. An extrusion die design example is solved by applying the design criterion of reducing the thickness of die wall. The results show that the structural lightweight design can significantly reduce the weight and increase the lightweight coefficient of extrusion die. To evaluate the effect of lightweight design on the environmental performances of the extrusion die, the life cycle assessment (LCA) is conducted. The stages of life cycle are composed of material stage, manufacture stage, use stage and end of life (EOL) stage. The environmental impacts (EIs) of the extrusion die are modelled as a function of geometrical and processing parameters. The EIs between the original and lightweight designed extrusion die are compared which shows that the proposed lightweight design method has a contribution to both material reduction and EIs of the extrusion die in the entire life cycle. It is foreseeable that the work in the thesis provides a foundation for dealing with lightweight design of conventional heavy duty machine components with complex functionalities.